2018
DOI: 10.1007/978-3-319-89963-3_5
|View full text |Cite
|
Sign up to set email alerts
|

What a Difference a Variable Makes

Abstract: We present an algorithm and tool to convert derivations from the powerful recently proposed PR proof system into the widely used DRAT proof system. The PR proof system allows short proofs without new variables for some hard problems, while the DRAT proof system is supported by top-tier SAT solvers. Moreover, there exist efficient, formally verified checkers of DRAT proofs. Thus our tool can be used to validate PR proofs using these verified checkers. Our simulation algorithm uses only one new Boolean variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In a more recent paper, we showed that there exists a polynomial-time procedure that translates PR proofs to DRAT proofs by introducing one new variable [11]. Moreover, we proved that extended resolution polynomially simulates the DRAT proof system [20].…”
Section: Open Problems and Future Workmentioning
confidence: 87%
See 1 more Smart Citation
“…In a more recent paper, we showed that there exists a polynomial-time procedure that translates PR proofs to DRAT proofs by introducing one new variable [11]. Moreover, we proved that extended resolution polynomially simulates the DRAT proof system [20].…”
Section: Open Problems and Future Workmentioning
confidence: 87%
“…We left these proofs out since they are twice as large as the PR proofs and their explanation is less intuitive. A recent result shows that the conversion of a PR proof into a DRAT proof requires only one auxiliary variable [11]. We can thus construct short DRAT proofs without new variables from short PR proofs without new variables.…”
Section: Short Proofs Of the Pigeon Hole Principlementioning
confidence: 99%
“…To verify the proofs for all our experiments, we did the following: We started with the PR proofs produced by our SDCL solver using the filtered positive reduct. We then translated them into DRAT proofs using the pr2drat tool [17]. Finally, we used the drat-trim checker to optimize the proofs (i.e., to remove redundant proof parts) and to convert them into the LRAT format, which is the format supported by the formally verified proof checker.…”
Section: Discussionmentioning
confidence: 99%
“…Our solver also produces PR proofs [19]. We certify their correctness by translating them via DRAT proofs [17] to LRAT proofs, which are then validated by a formally verified proof checker [18].…”
Section: Introductionmentioning
confidence: 99%
“…At this point there exists only an unverified checker to validate PR proofs, written in C. In order to increase the trust in the correctness of PR proofs, we implemented a tool to convert PR proofs into DRAT proofs [11], which in turn can be validated using verified proof checkers. Thanks to various optimizations, the size increase during conversion is rather modest on available PR proofs, thereby making this a useful certification approach in practice.…”
Section: Prefacementioning
confidence: 99%